2016
DOI: 10.14238/pi56.3.2016.162-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral versus rectal laxatives for functional constipation in child

Abstract: Background Functional constipation is a common childhood

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…142,145 The SRs explored outcomes including defaecation frequency, faecal incontinence, disimpaction, need for additional therapies and adverse events. 133,138 Within the primary studies, the most frequently reported outcomes of interest were defaecation frequency and faecal incontinence, reported by 14 [129][130][131][132][134][135][136][137][140][141][142]144,146,147 and 13 129,130,134,142,145,132,135,136,[139][140][141]144,146,147…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…142,145 The SRs explored outcomes including defaecation frequency, faecal incontinence, disimpaction, need for additional therapies and adverse events. 133,138 Within the primary studies, the most frequently reported outcomes of interest were defaecation frequency and faecal incontinence, reported by 14 [129][130][131][132][134][135][136][137][140][141][142]144,146,147 and 13 129,130,134,142,145,132,135,136,[139][140][141]144,146,147…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Gordon (2016) 133 pooled evidence from 25 RCTs 121,[124][125][126] ; we identified 10 more recent relevant RCTs 110,[129][130][131][132][135][136][137]140,139 (see Table 4). Four 135, 136,139,140 51…”
Section: What Are the Effects Of Laxatives?mentioning
confidence: 99%
See 1 more Smart Citation